GENERATIONAL DIVERSITY, PERSONAL ATTRIBUTES AND ORGANIZATIONAL COMMITMENT AMONG EMPLOYEES OF CORPORATE CONSULTANCIES - Purani Verasamy; Abdul Halim Abdul Majid; Noor Asma Jamaluddin (Jurnal Manajemen dan Kewirausahaan, 2021)
The main objective of this paper was to examine relationships of generational diversity, personal attributes (i.e., work values; attitudes and behavior; and interpersonal skills) on organizational commitment among employees of corporate consultancies. The research framework contained four independent variables which were generational diversity, work values, attitude and behavior, and interpersonal skills. Meanwhile the dependent variable was organizational commitment (i.e., affective, continuance and normative). The survey was conducted among employees of 15 corporate consultancies in Kuala Lumpur. A total of 436 questionnaires were distributed and 241 questionnaires were returned which represented a response rate of 55.27%. Statistical Package software for Social Science (SPSS) Version 24.0 was used to analyze the data. One-Way ANOVA and Pearson correlation coefficient were used to test the hypothesis. It was found that there was a significant difference among the three generations of workforce (i.e., Baby Boomers, generation X and generation Y) on organizational commitment (affective, continuance and normative). Further, the Pearson correlation coefficient revealed that there were significant relationships between work values, attitude and behavior, and interpersonal skills of the three generations (Baby Boomers, generation X and generation Y) towards organizational commitment (affective, continuance and normative).